A Comparative Study On The Effectiveness Of Mouthwash Using Intelligent System and Its Effect to COVID-19 (Global Journal of Sciences, 2024)
While COVID-19 is no longer the main public health challenge, we should still exercise  caution. The rapid spread of the virus in the past presented a significant threat to public health,  highlighting the need for continued vigilance and effective preventive measures. Over the years,  science-related groups, institutions, healthcare services, schools and companies have collaborated  in finding a common remedy to contain the virus. Therefore, there is a need of using safer products  to disinfect or prevent the presence of the virus in our environs.
Keywords: COVID-19; disintegrating; Coronavirus disease-2019